2013
DOI: 10.1063/1.4828459
|View full text |Cite
|
Sign up to set email alerts
|

Temperature effect on the small-to-large crossover lengthscale of hydrophobic hydration

Abstract: Abstract.The thermodynamics of hydration is expected to change gradually from entropic for small solutes to enthalpic for large ones. The small-to-large crossover lengthscale of hydrophobic hydration depends on the thermodynamic conditions of the solvent such as temperature, pressure, presence of additives, etc... We attempt to shed some light on the temperature dependence of the crossover lengthscale by using a probabilistic approach to water hydrogen bonding that allows one to obtain an analytic expression f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 47 publications
(28 reference statements)
0
17
0
Order By: Relevance
“…One of the greatest advances in our understanding of hydrophobicity is the recognition that the hydration structure and thermodynamics of non-polar solutes is length scale dependent [7,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. Although the length scale dependence of solvation is not unique to water [20,[28][29][30][31][32], arguably it is most pronounced for water because of the self-associated or "sticky" nature due to its H-bond network.…”
Section: Hydrophobicity -The Small and The Big Of Itmentioning
confidence: 99%
“…One of the greatest advances in our understanding of hydrophobicity is the recognition that the hydration structure and thermodynamics of non-polar solutes is length scale dependent [7,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. Although the length scale dependence of solvation is not unique to water [20,[28][29][30][31][32], arguably it is most pronounced for water because of the self-associated or "sticky" nature due to its H-bond network.…”
Section: Hydrophobicity -The Small and The Big Of Itmentioning
confidence: 99%
“…After equilibration the box lengths of the cubic boxes are roughly 5.65 nm and 7.15 nm for the small (6000 SPC/E) and big (12000 SPC/E) setups respectively. In order to gather enough statistics to probe long-time dynamics within the thin solvation shell comprised of O (10) to O(10 2 ) water molecules subsequent production runs have a length of 200 ns for the small systems and 100 ns for the big systems with a time step of 2 fs and writing period of 200 fs. Energy divergence is prevented by simulation in NVT ensemble (T = 300 K) applying the Nosé-Hoover thermostat with a coupling period of 1 ps.…”
Section: Planar Limitmentioning
confidence: 99%
“…One of the greatest advances in our understanding of the hydrophobic effect is the recognition that the hydration structure and thermodynamics of apolar solutes is qualitatively length scale dependent [1][2][3][4][5][6][7][8][9][10][11]. The microscopic reason is that water structures very differently at small (convex) solutes, where the bulk H-bond network is only moderately deformed, as compared to large solutes, which significantly distort the tetrahedral bulk structure.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that hydrophobicity plays a pivotal role in a number of key physical and biological processes and often it has been found that hydrophobicity is length-scale dependent. Here, we expand our recent work on water–ethanol binary mixtures by systematically exploring the role of the chain length of alcohol (methanol to butanol) on the composition-dependent pair hydrophobicity in their aqueous mixtures. We have shown that the composition at which the pair hydrophobicity is highest is dependent on the alcohol chain length in water–alcohol binary mixtures.…”
Section: Introductionmentioning
confidence: 99%